(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: According to the World Health Organization (WHO), breastfeeding is the ideal food for new-borns up to six months of age. It provides all the nutritional needs of infants and protects them from many childhood illnesses. Therefore, the current study results provided baseline data of those mothers who may not breastfeed due to a lack of milk production or insufficient intake of proper nutrients, which may worsen this condition. Aim: The study aimed to explore challenges and issues faced by Agalactorrhric mothers in Matta Swat Hospital, Pakistan. Methods: Using purposive sampling and in-depth interviews, a descriptive phenomenological design explored the lived experiences of 13 agalactorrheic mothers at a Category C Hospital in Matta, Swat. Mothers with known medical conditions or who were unwilling to participate were excluded. Data were collected using a semi-structured, audio-recorded interview guide. Braun and Clarke’s six-phase thematic analysis was used to analyze the data. Result: The data identified 128 open codes. Additional and unnecessary codes were omitted, resulting in the identification of 18 categories from the open codes. From these categorical data, significant themes emerged, which were listed as follows: insufficient nourishment, physical and health discomfort, financial strain, emotional and psychological consequences, and alternative feeding complexities. Conclusion: This was a comprehensive study that highlighted challenges and issues faced by Agalactorrhric mothers. It revealed that financial constraints and inadequate access to nutritious food can significantly impact milk production, leading to adverse effects on both milk production and the baby’s health. Additionally, the findings highlighted significant hardships mothers face due to societal and familial pressures. Financial burden is a key factor contributing to insufficient milk production among Agalactorrhric mothers.